Unveiling game meat: an analysis of marketing mix and consumer preferences for a forest ecosystem product - Riedl, Marcel; Němec, Martin; Jarský, Vilém; Zahradník, Daniel (Frontiers in Sustainable Food Systems, 2024)
This study explores the dynamics of the game meat market, with a particular focus on venison and wild boar meat, to assess the impact of a nuanced marketing mix and strategy grounded in a comprehensive customer analysis. By conducting three pivotal research studies-namely, the Omnibus Survey (2022) and Consumer Market Analysis Polls (2021 & 2023)-and analysing their data, this research comprehensively analyses buyers' preferences, motivations, and purchasing patterns. This paper is guided by three research questions aimed at examining the relationship between the game meat consumption and engagement in forest ecosystem services, including forest visitation, the sociodemographic characteristics of consumers and the criteria for market segmentation. The analysis focuses on identifying factors influencing the game meat consumption and examines how these factors may influence consumer behaviour over time. It also explores the implications for the development of marketing strategies, based on Michael E. Porter's approach, which is discussed in detail.Additionally, the research evaluates the role of game meat within the context of forest ecosystem services, its contribution to forest reforestation initiatives, and its relevance in the formulation of forest policy. This examination highlights the dual nature of game meat as both a market commodity and a critical element in ecosystem management and policy frameworks, seeking to harmonise the economic and ecological objectives.